Introduction to vascular ultrasonography - Zwiebel, William J; Pellerito, John S (Saunders/Elsevier, 2012)
Now in its 6th edition, Introduction to Vascular Ultrasonography, by Drs. John Pellerito and Joseph Polak, provides an easily accessible, concise overview of arterial and venous ultrasound. A new co-editor and new contributors have updated this classic with cutting-edge diagnostic procedures as well as new chapters on evaluating organ transplants, screening for vascular disease, correlative imaging, and more. High-quality images, videos, and online access make this an ideal introduction to this complex and rapidly evolving technique.